Sonchus oleraceus L.: ethnomedical, phytochemical and pharmacological aspects - Sánchez-Aguirre, Oscar Antonio; Sánchez-Medina, Alberto; Juárez-Aguilar, Enrique; Barreda-Castillo, José Martín; Cano-Asseleih, Leticia Margarita (Naunyn-Schmiedeberg's archives of pharmacology, 2024)
Sonchus oleraceus L. (Asteraceae) is a cosmopolitan species native to Europe commonly known as lettuce, sowthistle, chicory, or fake dandelion, considered a weed. However, for many years in various cultures around the world, it has been used as food and medicinal plant. The aim of this integrative review is to document the ethnomedical, phytochemical, and pharmacological information of this species. Forty-one papers document the use of S. oleraceus to heal of a wide variety of diseases. However, gastrointestinal problems, diabetes, inflammation, infections, hepatitis, wounds, and to consume it as food are the most common uses. On the other hand, only 11 items highlight that the main groups of secondary metabolites in this species are flavonoids and terpene lactones. Finally, 45 items reveal that antioxidant, antimicrobial, antiproliferative and cytotoxic were the most studied pharmacological activities. In vitro and in vivo studies of extracts and components isolated from different parts of S. oleraceus have provided a concrete overview of the pharmacological properties of this species that supports its ethnomedical uses in cultures from different parts of the world. The reports of this species have focused solely on the study of the complete plant, leaves, and aerial parts, so it is necessary to study other parts of this species to search for bioactive compounds. No clinical studies were found, which creates an opportunity to expand scientific knowledge of this species. Graphical Abstract